Targeting of CD22-positive B-cell lymphoma cells by synthetic divalent sialic acid analogues - Schweizer, Astrid; Brossmer, Reinhard (European journal of immunology, 2012)
CD22 is an inhibitory co-receptor of the B-cell receptor (BCR) on B cells. Since CD22 is ubiquitously expressed in the B-cell lineage and CD22 endocytosis can be triggered efficiently, antibodies and antibody-based immunotoxins against CD22 are used to target B cells both in B-cell lymphomas and leukemias, as well as in autoimmune diseases. CD22 recognizes α2,6-linked sialic acids as endogenous ligands. We have developed new synthetic sialosides as ligands for human CD22. These sialosides bind CD22 on human B cells with high affinity and can efficiently enhance IgM-triggered Ca2+ signaling. We coupled these sialosides to Pseudomonas exotoxin A to generate a novel CD22 ligand-based immunotoxin. This sialoside-exotoxin-A construct can specifically kill CD22-positive B-cell lymphoma cells. It binds specifically to CD22-positive B-cell lymphoma cells and is dominant over endogenous cis-ligands on the B-cell surface. The sialoside-exotoxin-A construct is efficiently internalized by endocytosis into B-cell lymphoma cell lines. Thus we show the development of a new therapeutic compound for targeting CD22 on human B cells, both for B-cell lymphoma, as well as for B-cell-mediated autoimmune diseases.